How to squat? Effects of various stance widths, foot placement angles and level of experience on knee, hip and trunk motion and loading - Silvio Lorenzetti; Mira Ostermann; Fabian Zeidler; Pia Zimmer; Lina Jentsch; Renate List; William R. Taylor; Florian Schellenberg (BMC, 2018)
Abstract Background Squatting is a core exercise for many purposes. The tissue loading during squatting is crucial for positive adaptation and to avoid injury. This study aimed to evaluate the effect of narrow, hip and wide stance widths, foot position angles (0°, 21°, and 42°), strength exercise experience, and barbell load (0 and 50% body weight, experts only) during squatting. Methods Novice (N = 21) and experienced (N = 21) squatters performed 9 different variations of squats (3 stance widths, 3 foot placement angles). A 3D motion capture system (100 Hz) and two force plates (2000 Hz) were used to record mediolateral knee displacement (ΔD*), range of motion (RoM) at the hip and knee joints, and joint moments at the hip, knee, and lower back. Results Both stance width and foot placement angles affected the moments at the hip and knee joints in the frontal and sagittal planes. ΔD* varied with stance width, foot placement angles and between the subjects' level of experience with the squat exercise as follows: increasing foot angle led to an increased foot angle led to an increased ΔD*, while an increased stance width resulted in a decreased ΔD*; novice squatters showed a higher ΔD*, while additional weight triggered a decreased ΔD*. Conclusions Suitable stance width and foot placement angles should be chosen according to the targeted joint moments. In order to avoid injury, special care should be taken in extreme positions (narrow stand-42° and wide stance-0°) where large knee and hips joint moments were observed.